1992
DOI: 10.1182/blood.v80.1.60.bloodjournal80160
|View full text |Cite
|
Sign up to set email alerts
|

Blasts from patients with acute myelogenous leukemia express functional receptors for stem cell factor

Abstract: Stem cell factor (SCF) acts in concert with lineage-specific growth factors to stimulate the growth of hematopoietic colonies. To determine if neoplastic human hematopoietic cells would also respond to SCF, we cultured marrow mononuclear cells from 20 patients with newly diagnosed acute myelogenous leukemia (AML) and two normal donors with SCF, interleukin 3 (IL-3), granulocyte-macrophage colony-stimulating factor (GM-CSF), or combinations of growth factors in semisolid medium, and assessed colony growth. SCF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…The K d value of rdhSCF (29.4 pm,) was higher than that of rhSCF (45.2 pm). This result agreed with other published results about the binding affinity of SCF to its receptor (8,27,28), indicating that higher binding affinity to receptor should be responsible for After incubation, the activity was assayed as described under ÔMaterials and methodsÕ. The ED50 of rdhSCF, E. coliderived rhSCF and insect-derived rhSCF were 0.33, 2.87 and 3.03 ng/mL, respectively.…”
Section: Resultssupporting
confidence: 88%
“…The K d value of rdhSCF (29.4 pm,) was higher than that of rhSCF (45.2 pm). This result agreed with other published results about the binding affinity of SCF to its receptor (8,27,28), indicating that higher binding affinity to receptor should be responsible for After incubation, the activity was assayed as described under ÔMaterials and methodsÕ. The ED50 of rdhSCF, E. coliderived rhSCF and insect-derived rhSCF were 0.33, 2.87 and 3.03 ng/mL, respectively.…”
Section: Resultssupporting
confidence: 88%
“…The broad range of expression of these receptors could, however, correlate with the heterogeneous response of the cells to growth factors described in other reports. IL-3 (38,39), SCF (31,41), IL-6 (35, 42) and G-CSF (36,43) stimulated the proliferation of the leukaemic cells in only some of the AML patients. IL-3 (40,44,45) and IL-7 (46±48) induced a proliferative response in part of the B-lineage ALL samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, AML and B-lineage ALL CD34 + cells expressed the same growth factor receptors as their normal counterparts, but often at different levels. In other reports, the receptor expression on the leukaemic cells seemed not to be different from normal, but mononuclear cell suspensions were examined and these contained different cell types and maturation stages (30,31). When a cut-off for positivity was set at 20% of positive cells, all AML samples could be identi®ed Reactivity expressed as percentage of CD34 + bone marrow cells and as percentage of acute leukaemia samples.…”
Section: Discussionmentioning
confidence: 99%
“…The ligand of KIT, stem cell factor (SCF), promotes growth and colony-formation of myeloid progenitor cells as well as the differentiation of MC (Zsebo et al, 1990;Tsai et al, 1991;Valent et al, 1992;Kirshenbaum et al, 1992). It has also been described that in a group of patients with AML, blast cells express KIT and grow in response to the KIT-ligand SCF (Bü hring et al, 1991;Broudy et al, 1992). A number of previous and more recent studies have shown that certain somatic mutations in KIT can lead to autophosphorylation of the receptor and consecutive autonomous growth of affected cells (Furitsu et al, 1993;Ashman et al, 2000;Feger et al, 2002).…”
Section: Introductionmentioning
confidence: 99%